Register in TED Lasso Serries Season One Pilot Episode: A Sociolinguistics Analysis - Yanthy Mardiana; Ervina C M Simatupang (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This research focused on register used in the Ted Lasso series, pilot episode in season one. The research aims at identifying (1) register used in the episode and (2) components of ethnography of communication that occur within the context of register usage. The primary source of data for this descriptive qualitative is the script used in the pilot episode of first season of Ted Lasso. The stage of the research consists of following steps: Watching the pilot episode of the Ted Lasso series, transcribing the dialogue used, analyzing the registers used and rewatching the episode to confirm the context to validate the register and the components of ethnography of communications occurred. The theoretical framework used in this research comes from Joos (1972) about five registers based on the formality, namely (1) Frozen, (2) Deliberative, (3) Consultative, (4) Casual and (5) intimate. The supporting theoretical for this research is about the ethnography of communication based on S.P.E.A.K.I.N.G theory of Hymes (1972) explaining eight components of the ethnography of communications, (1) Setting and Scene, (2) Participants, (3) Ends, (4) Act Sequence, (5) Key, (6) Instrumentalities, (7) Norms and (8) Genres. The research shows that there are only three registers occurred in the pilot episode with one formal register, six consultative registers and four casual registers. For the ethnography of communications occurred, there are four components that occurred in all register usage, namely the participants, ends, act sequence and instrumentalities.